Special AT‐rich sequence binding protein 1 promotes multidrug resistance in gastric cancer by regulation of Ezrin to alter subcellular localization of ATP‐binding cassette transporters. Issue 4 (11th January 2023) - Luo, Jiajun; Yuan, Jingwen; Yang, Yu; Jiang, Yue; Yan, Junfeng; Tong, Qiang
Abstract: Multidrug resistance is a primary factor in the poor response to chemotherapy and subsequent death in gastric cancer patients. However, the molecular mechanisms involved remain unclear. In this study, the high expression of special AT‐rich sequence binding protein 1 (SATB1) in gastric cancer was found to be associated with reduced sensitivity to various chemotherapy drugs. Our results demonstrate that SATB1 can promote chemotherapy resistance in gastric cancer in vitro and in vivo. SATB1 exerts its effect by enhancing the activity of multiple ATP‐binding cassette (ABC) transporters (P‐glycoprotein, multidrug resistance‐associated protein, and breast cancer resistance protein) in gastric cancer cell lines. We also found that SATB1 affects ABC transporters by altering the subcellular localization of the ABC transporter rather than its expression. Subsequently, we confirmed that Ezrin binds to various ABC transporters and affects their subcellular localization. In addition, we found that SATB1 can also bind to the Ezrin promoter and regulate its expression. In the present study, we elucidate the mechanism of SATB1‐mediated multidrug resistance in gastric cancer, providing a basis for SATB1 as a potential target for reversal of resistance. Abstract : SATB1 can enhance the membrane localization of multiple ABC transporters by upregulating Ezrin expression in gastric cancer cells, thereby promoting multidrug resistance in gastric cancer.